Perioperative Cerebral Microbleeds After Adult Cardiac Surgery. Issue 2 (February 2019) - Patel, Nikil; Banahan, Caroline; Janus, Justyna; Horsfield, Mark A.; Cox, Anthony; Li, Xingfeng; Cappellugola, Laurie; Colman, Jordan; Egan, Vincent; Garrard, Peter; Chung, Emma M.L.
Abstract : Background and Purpose—: Cerebral microbleeds (CMBs) have been observed using magnetic resonance imaging in patients with cardiovascular risk factors, cognitive deterioration, small vessel disease, and dementia. They are a well-known consequence of cerebral amyloid angiopathy, chronic hypertension, and diffuse axonal injury, among other causes. However, the frequency and location of new CMBs postadult cardiac surgery, in association with cognition and perioperative risk factors, have yet to be studied. Methods—: Pre- and postsurgery magnetic resonance susceptibility-weighted images and neuropsychological tests were analyzed from a total of 75 patients undergoing cardiac surgery (70 men; mean age, 63±10 years). CMBs were identified by a neuroradiologist blinded to clinical details who independently assessed the presence and location of CMBs using standardized criteria. Results—: New CMBs were identified in 76% of patients after cardiac surgery. The majority of new CMBs were located in the frontal lobe (46%) followed by the parietal lobe (15%), cerebellum (13%), occipital lobe (12%), and temporal lobe (8%). Patients with new CMBs typically began with a higher prevalence of preexisting CMBs ( P =0.02). New CMBs were associated with longer cardiopulmonary bypass times ( P =0.003), and there was a borderline association with lower percentage hematocrit ( P =0.04). Logistic regression analysis suggested a ≈2% increase in the odds of acquiring new CMBs during cardiac surgery for every minute of bypass time (odds ratio, 1.02; 95% CI, 1.00–1.05; P =0.04). Postoperative neuropsychological decline was observed in 44% of patients and seemed to be unrelated to new CMBs. Conclusions—: New CMBs identified using susceptibility-weighted images were found in 76% of patients who underwent cardiac surgery. CMBs were globally distributed with the highest numbers in the frontal and parietal lobes. Our regression analysis indicated that length of cardiopulmonary bypass time and lowered hematocrit may be significant predictors for new CMBs after cardiac surgery. Clinical Trial Registration—: URL:http://www.isrctn.com . Unique identifier: 66022965. Abstract : Supplemental Digital Content is available in the text.